2020
DOI: 10.1101/2020.04.27.20081562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence of COVID-19 and Connections with Air Pollution Exposure: Evidence from the Netherlands

Abstract: HighlightsBackground: Research on viral respiratory infections has found that infection risks increase following exposure to high concentrations of particulate matter. Several hot-spots of Severe Acute Respiratory Syndrome Coronavirus 2 infections are in areas associated with high levels of air pollution.Approach: This study investigates the relationship between exposure to particulate matter and COVID-19 incidence in 355 municipalities in the Netherlands using data on confirmed cases and hospital admissions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 32 publications
8
60
0
2
Order By: Relevance
“…In addition to the Wu et al (2020) study, another American ecological study based on approximately 3000 counties found that nitrogen dioxide (NO 2 ) was significantly associated with COVID-19 mortality and case-fatality rates, while PM 2.5 exhibited a marginally significant association with mortality ( Liang et al, 2020 ). A significant positive association of PM 2.5 with COVID-19 incidence and hospital admissions was also reported in the Netherlands ( Andree, 2020 ). Ogen (2020) reported co-location of high NO 2 concentrations estimated from remote sensing and high COVID-19 mortality counts in northern Italy and Madrid.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In addition to the Wu et al (2020) study, another American ecological study based on approximately 3000 counties found that nitrogen dioxide (NO 2 ) was significantly associated with COVID-19 mortality and case-fatality rates, while PM 2.5 exhibited a marginally significant association with mortality ( Liang et al, 2020 ). A significant positive association of PM 2.5 with COVID-19 incidence and hospital admissions was also reported in the Netherlands ( Andree, 2020 ). Ogen (2020) reported co-location of high NO 2 concentrations estimated from remote sensing and high COVID-19 mortality counts in northern Italy and Madrid.…”
Section: Discussionsupporting
confidence: 57%
“…Notably SARS-CoV-1 patients from more polluted regions were twice as likely to die as those in less polluted places ( Cui et al, 2003 ). There is also evidence that air pollution exposure more generally adversely affects respiratory immune defences ( Domingo and Rovira, 2020 ; Yang et al, 2020 ), and emerging evidence suggesting that novel coronavirus disease (COVID-19) incidence and mortality may be increased in relation to both acute ( Zhu et al, 2020 ) and chronic exposure ( Andree, 2020 ; Liang et al, 2020 ; Ogen, 2020 ; Wu et al, 2020 ). This evidence implies that deterioration in air quality over short time periods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In another posted study by the World Bank Group, Andrée conducted an ecological analysis of incident COVID-19 cases against annual average concentrations of across 355 municipalities in the Netherlands ( Andrée 2020 ). The analyses comprised 4,004 confirmed cases of COVID-19 until 22 March 2020 for which residential addresses were available.…”
Section: Resultsmentioning
confidence: 99%
“…( 2020 ) (China, posted 10 April 2020). The fourth nonpeer reviewed study ( Andrée 2020 ) was a policy working paper published by the World Bank (data from the Netherlands, posted in April 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, all these event or incidence dramatically changed the over economic systems, way of governing nations and even changed our literature as well. Even all these incidences changed the lifestyle of the entire world, similarly, the ongoing pandemic crises of covid-19 will have a permanent and everlasting impact on our lives [1,2].…”
Section: Introductionmentioning
confidence: 99%